1999
DOI: 10.1007/s11881-999-0020-2
|View full text |Cite
|
Sign up to set email alerts
|

Developmental dyslexia: Related to specific or general deficits?

Abstract: The present study was designed to examine the question of whether developmental dyslexia in 12-year-old

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 32 publications
6
26
0
Order By: Relevance
“…Many studies have reported that individuals with dyslexia perform more poorly on pseudoword repetition than control participants (e.g. Brady, Poggie, & Rapala, 1989;Brady, Shankweiler, & Mann, 1983;Hulme & Snowling, 1992;Kamhi & Catts, 1986;Snowling, 1981;Snowling, Goulandris, Bowlby, & Howell, 1986;Van Bon & Van Der Pijl, 1997;Van Daal & van der Leij, 1999), compatible with the notion that a phonological core deficit provides a causal explanation for dyslexia. But note that Reis and Castro-Caldas (1997) found that illiterates also performed much worse than literates on pseudoword repetition (replicated in Castro-Caldas, Petersson, Reis, Stone-Elander, & Ingvar, 1998).…”
Section: Pseudoword Repetitionmentioning
confidence: 71%
“…Many studies have reported that individuals with dyslexia perform more poorly on pseudoword repetition than control participants (e.g. Brady, Poggie, & Rapala, 1989;Brady, Shankweiler, & Mann, 1983;Hulme & Snowling, 1992;Kamhi & Catts, 1986;Snowling, 1981;Snowling, Goulandris, Bowlby, & Howell, 1986;Van Bon & Van Der Pijl, 1997;Van Daal & van der Leij, 1999), compatible with the notion that a phonological core deficit provides a causal explanation for dyslexia. But note that Reis and Castro-Caldas (1997) found that illiterates also performed much worse than literates on pseudoword repetition (replicated in Castro-Caldas, Petersson, Reis, Stone-Elander, & Ingvar, 1998).…”
Section: Pseudoword Repetitionmentioning
confidence: 71%
“…Phonological awareness. In transparent orthographies, such as German and Dutch, phonological awareness tasks are known to reach ceiling levels in accuracy in primary school children, even in those with dyslexia (Landerl & Wimmer, 2000;van Daal & van der Leij, 1999). Therefore, the present study considered reaction time (of the correct trials) as the dependent variable in the phonological awareness tasks.…”
Section: Methodsmentioning
confidence: 99%
“…Among the phonological memory tasks with which children with dyslexia have difficulty is the nonword repetition task, in which participants must store and repeat a phonological sequence that could be a word in the language but is not. Research has shown that children with dyslexia consistently perform less well than control participants on nonword repetition tasks (Brady, Poggie, & Rapala, 1989;Catts, 1986;Hulme & Snowling, 1992;Kamhi & Catts, 1986;Snowling, 1981;van Daal & van der Leij, 1999;van der Bob & van der Pijl, 1997). Studies have also demonstrated that heritability for dyslexia is higher when the disorder is combined with a deficit in nonword repetition (Bishop, 2001;Bishop, Adams, & Norbury, 2004;Raskind, Hsu, Berninger, Thomson, & Wijsman, 2000).…”
Section: Dyslexiamentioning
confidence: 99%